Resection with preserved histologic morphology of a rare tumour via bronchoscopic cryosurgery - Tan, Jessica Han Ying; Takano, Angela Maria; Hsu, Anne Ann Ling (Journal of Thoracic Disease, 2016)
Tracheobronchial leiomyoma is a rare pulmonary neoplasm accounting for